2007
DOI: 10.1021/cg070180p
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of a Lamellar Sr3Ru2O7–Sr4Ru3O10 Eutectic System

Abstract: Lamellar eutectic crystals of Sr 3 Ru 2 O 7 -Sr 4 Ru 3 O 10 have been successfully grown in a double-mirror optical floating zone furnace in the flux feeding floating zone configuration with Ru self-flux. The synthesis procedure of the polycrystalline rod is found to be a critical factor for the crystal growth. The eutectic dark-brown crystals grow in the [100] direction and cleave in the a-b plane as the single phase crystals. The morphology, structure, phase purity, and composition of the samples were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
(88 reference statements)
1
19
0
Order By: Relevance
“…In this respect, we mention that Sr 2 RuO 4 /Sr 3 Ru 2 O 7 [18,19] and Sr 3 Ru 2 O 7 /Sr 4 Ru 3 O 10 [20] eutectics have been achieved. The investigation of the collective behavior of the eutectic phases indicates a relevant role of the interface physics, and their superconducting and magnetic properties turn out to differ markedly if compared to the homogeneous single crystalline ones [21][22][23].…”
Section: Introductionmentioning
confidence: 82%
“…In this respect, we mention that Sr 2 RuO 4 /Sr 3 Ru 2 O 7 [18,19] and Sr 3 Ru 2 O 7 /Sr 4 Ru 3 O 10 [20] eutectics have been achieved. The investigation of the collective behavior of the eutectic phases indicates a relevant role of the interface physics, and their superconducting and magnetic properties turn out to differ markedly if compared to the homogeneous single crystalline ones [21][22][23].…”
Section: Introductionmentioning
confidence: 82%
“…Details on the growth methodology are given elsewhere [27,30,31]. Composition, crystalline structure, and quality of the crystals were checked by means of energy dispersive spectroscopy, scanning electron microscopy, polarizedlight optical microscopy, electron backscattered diffraction, specific heat, x-ray diffraction, and susceptibility measurements.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, by the same analysis, we got on bright contrast region of sample B a Sr/Ru ratio of 1.48(3) (corresponding to Sr 3 Ru 2 O 7 ) while a ratio of 1.32(2) (corresponding to Sr 4 Ru 3 O 10 ) has been measured in dark area. The EBSD measurements performed along the polished (a-b) plane of samples B showed the presence of wavy interfaces at the boundary between the Sr 3 Ru 2 O 7 and the Sr 4 Ru 3 O 10 [9].…”
Section: Resultsmentioning
confidence: 96%
“…The rod and seed crystal were www.crt-journal.org rotated oppositely to each other at 30 rpm. An inspection of the surface of several samples under a differential interference contrast microscope in polarized light showed that the crystal morphology was mainly constituted by ordered lamellar pattern or isolated islands of one phase embedded in the other [8,9,11]. X-ray diffraction spectra of sample A and sample B with different ratio of the two phases are shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation